Lacustrine Environment: Pollution and Remediation - Prof. G. C. Pandey; Dr. Vijay Kumar Upadhyay; Dr. Sandeep Kumar (International Journal of Scientific Research in Science and Technology, 2025)
A lacustrine environment refers to the ecosystem of a lake or a body of standing freshwater. These environments play an essential role in supporting biodiversity, regulating local climates, and providing water for drinking, agriculture, and recreation. However, like many ecosystems, they are vulnerable to pollution, which can severely degrade water quality, harm aquatic life, and disrupt the services they provide.
Keywords: Lacustrine; Environment; Pollution; Management; Nutrient